PENGARUH PUPUK OSTINDO DAN DEFOLIASI DAUN TERHADAP HASIL JAGUNG (Zea mays L.) - Fadli, Mohamad; Rochyat, Erwin Arief; Yuki, Yuki (Jurnal Magrobis, 2019)
This study aims to determine the effect of ostindo fertilizer and leaf defoliation on corn  yield (Zea masy L.). The study began in October 2018 until January 2019, located in the village of Bendang Raya, Tenggarong District, Kutai Kartanegara Regency. This study was arranged in a Randomized Complate Block Design (RCBD) with a 4 x 3 factorial analysis with replications three times. The first factor for giving ostindo fertilizer (p) consisted of 3 levels, namely, p0 (untreated control), p1 (45 g plot-1), and p2 (90 g plot-1) and the second factor leaf defoliation (d) that is, d0 (control without treatment), d1 (70 days), d2 (77 days), and d3 (84 days).The results showed that ostindo fertilizer removal had no significant effect on the parameters of observation of plant height, leaf defoliation weight, ear weight without weight per plant, weight of crop seeds, including the weight of 100 seeds. With the highest yield average dry weight per hectare (t ha-1), that is in treatment p1 (45 g plot-1) which is 4.65 t ha-1 whereas for the lowest yield dry weight shelled per hectare (t ha-1) is treatment p0 (without treatment) with an average yield of 4.47 t ha-1.Then the treatment of leaf defoliation did not significantly affect the parameters of observation of  ear weight without plant per plant, weight of planting seeds, weight of 100 seeds and dry weight per hectare (t ha-1) ie, the highest yield was obtained from the average shelled dry weight per hectare (t ha-1), that is in treatment d1 (70 days after planting) which is 4.80 t ha-1 whereas for the lowest yield dry weight per hectare  (t ha-1) is treatment d0 (without treatment) with an average average 4.40 t ha1.The interaction between ostindo fertilizer and leaf defoliation had no significant effect on all parameters observed, the highest average yield of dry weight per hectare (t ha-1) in treatment p1d1 (45 g plot-1 and 70 days after planting) with an average yield 4.87 t ha-1. The lowest yield was dry shelled weight per hectare (t ha-1) in p2d3 treatment (90 g plot-1 and 83 days after planting) with an average yield of 4.23 t ha-1. Key word :  Ostindo fertilizer, leaf defolition, corn yield